Peri-operative Research Living on the cutting edge: (The compelling culture of OR nursing) - Wood, Heather (Operating Room Nurses Association of Canada Journal, 1991)
Operating room nursing is a unique, challenging, and often satisfying career. Operating room nurses like the feeling of “living on the cutting edge.” They like the challenge of a highly skilled and co- ordinated atmosphere. They like the respect they engender in their colleagues for their mastery of the skills inherent to operating room nursing. The purpose in conducting this study was to identify variables that attract, maintain nurses’ interest in, and foster work satisfaction within the operating room setting.